OpenFOAM reduced channel modeling análisis - Lara Pérez, Mónica Yineth; Nova Burgos, Elías Daniel David; Montenegro Carrillo, Martha Patricia; Tibidor Jara, Angélica María (Ingeniería Solidaria, 2023)
Introduction: The article is a product of the research “Analysis of open channel models with reduction in Openfoam” developed at Universidad Santo Tomás in 2022 integrating computational fluid dynamics (cfd), in an open channel with reduction of multiphase, isotropic, isothermal, turbulent and steady state flow.Problem: Drinking water supply requires efficient treatment, and to achieve this, the hydrodynamic and physicochemical processes of the treatment plant units must be known in detail. Simulation is used to reduce costs and to perform multiple experiments. A robust hydraulic parameter readout system increases the reliability of modeling [1]. The larger source of experimental data leads to a more reliable model.Objective: Familiarize the reader with the tools for learning and optimization of conventional treatment systems for human water supply. Research also contributes to ensuring environmental sustainability and reducing the proportion of people without sustainable access to water and sanitation services, especially in rural areas where lack of water infrastructure is a prevalent problem.Method: Simulation of complex turbulence models by means of energy, mass and momentum conservation equations by means of Openfoam solvers.Results: There is a convergence since time 5952, since after this time most of the residual limit values are in the order of 10-3 and 10-4, and taking into account the state of the art which states that the solution has converged if the residual is in the order of these valuesConclusions: A contribution has been made to the knowledge of computational fluid dynamics, generating an approach to the modeling of channels to the students of the civil engineering faculty of the Santo Tomas University, for advances in future research, thus strengthening in an institutional way the use of Openfoam for the modeling of complex problems in water transport systems.